Answer:
2
Step-by-step explanation:
Use pemdas
4a*(3-2b)
4(1/2)*(3-2(-1))
4* 1/2 = 2
2*(3-2(-1)
-2*-1 = 2
2(3-2)
3 -2 = 1
2(1) = 2
The questions where asking to compute for the derivative of x->a, and base on my own calculation and further computation about the said function, the derivative of x->a is <span>\[f'(x)=-6x-5\] and if you replace x by 1 here you will get
\[f'(1)=-11\]. I hope you are satisfied with my answer and feel free to ask for more </span>
Answer:
Yes!
Step-by-step explanation:
To find the area, multiply the sides.
6.4x10.5+67.2
Then subtract
67.2-60=7.2
There is still 7.2 ft² after the sow.
Step-by-step explanation:
please rate brainliest
Answer:
The function in the form of fog(x) is written as 48 x² + 336 x + 590
Step-by-step explanation:
Given function as :
f(x) = 3 x² - 6 x + 5
g(x) = - 4 x - 13
So, The function in the form of fog(x) is written as
We, substitute the value of g(x) into f(x)
∴ fog(x) = 3 (g(x))² - 6 (g(x)) + 5
Or, fog(x) = 3 (- 4 x - 13 )² - 6 ( - 4 x - 13 ) + 5
or, fog(x) = 3 (16 x² + 169 + 104 x) + 24 x + 78 + 5
or , fog(x) = 48 x² + 507 + 312 x + 24 x + 78 + 5
or , fog(x) = 48 x² + 336 x + 590
So, The function in the form of fog(x) = 48 x² + 336 x + 590
Hence The function in the form of fog(x) is written as 48 x² + 336 x + 590 Answer